2020
DOI: 10.1155/2020/1718541
|View full text |Cite
|
Sign up to set email alerts
|

Developing a New Spatial Unit for Macroscopic Safety Evaluation Based on Traffic Density Homogeneity

Abstract: Macrolevel crash modeling has been extensively applied to investigate the safety effects of demographic, socioeconomic, and land use factors, in order to add safety knowledge into traffic planning and policy-making. In recent years, with the increasing attention to regional traffic management and control, the safety effects of macrolevel traffic flow parameters may also be of interest, in order to provide useful safety knowledge for regional traffic operation. In this paper, a new spatial unit was developed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Many driving simulators have been designed, from the low-level ones that allow the drivers to control the hand brake of their car [6], to higher-level ones, in which the drivers can control their car acceleration and lane-change [7]. Some simulators model the traffic in an urban road network [8], some others model car's intersection access [9][10][11][12], or roundabout insertion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many driving simulators have been designed, from the low-level ones that allow the drivers to control the hand brake of their car [6], to higher-level ones, in which the drivers can control their car acceleration and lane-change [7]. Some simulators model the traffic in an urban road network [8], some others model car's intersection access [9][10][11][12], or roundabout insertion [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, here is where it relies on the importance of creating a method to assess crash occurrence using specialized methods to forecast crash frequencies. A handful of studies focused on identifying risk factors of crash occurrence using historical data at the TAZ level ( 1720 ). For instance, Wang et al showed that at the macro-level—for example, TAZ and census tract—traffic flow influenced crash occurrence, by using Bayesian models to account for the spatial dependency ( 20 ).…”
mentioning
confidence: 99%
“…A handful of studies focused on identifying risk factors of crash occurrence using historical data at the TAZ level ( 1720 ). For instance, Wang et al showed that at the macro-level—for example, TAZ and census tract—traffic flow influenced crash occurrence, by using Bayesian models to account for the spatial dependency ( 20 ). Peera et al studied the relationship among land-use characteristics and traffic accidents at the TAZ level using a generalized linear regression model ( 17 ).…”
mentioning
confidence: 99%